2008
DOI: 10.1084/jem2054oia10
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear envelope defects cause stem cell dysfunction in premature-aging mice

Abstract: Abbreviations used in this paper: 5mC, 5-methylcytosine; LRC, label-retaining cell; Mitf, microphthalmia transcription factor; TPA, tetradecanoylphorbol 13-acetate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 18 publications
3
51
0
Order By: Relevance
“…In one study, microarray of Zmpste24 -/cells indicated upregulation of the p53 tumor suppressor pathway that may predispose HGPS fibroblasts to early senescence (Varela et al, 2005). The absence of ZMPSTE24-mediated cleavage of lamin A has also been linked to aberrant stem cell maintenance, a mechanism that may contribute to the defects observed in patients in tissues that rely heavily on stem cell niches, such as hair and skin (Espada et al, 2008;Scaffidi and Misteli, 2008). This might reflect an initial prosurvival strategy that eventually becomes detrimental to the cells and tissues.…”
Section: Potential Disease Mechanisms Resulting From a Lack Of Zmpstementioning
confidence: 99%
“…In one study, microarray of Zmpste24 -/cells indicated upregulation of the p53 tumor suppressor pathway that may predispose HGPS fibroblasts to early senescence (Varela et al, 2005). The absence of ZMPSTE24-mediated cleavage of lamin A has also been linked to aberrant stem cell maintenance, a mechanism that may contribute to the defects observed in patients in tissues that rely heavily on stem cell niches, such as hair and skin (Espada et al, 2008;Scaffidi and Misteli, 2008). This might reflect an initial prosurvival strategy that eventually becomes detrimental to the cells and tissues.…”
Section: Potential Disease Mechanisms Resulting From a Lack Of Zmpstementioning
confidence: 99%
“…Together, these results are consistent with earlier studies where heterozygous Lef1 mice show diminished bone mass and those null for Lef1 are post-nataly growth retarded, have defective hair and tooth formation, tissues markedly affected in progeria (Noh et al, 2009; van Genderen et al, 1994). In addition, in Zmpste24 null mice, where Lamin A remains farnesylated, Wnt signaling is reduced in hair follicles (Espada et al, 2008). …”
Section: Discussionmentioning
confidence: 99%
“…In support of this model, expression of progerin in skin cells resulted in impaired function and depletion of epidermal stem cells, as well as downregulation of both the Notch and Wnt signalling pathways [66]. Downregulation of the Wnt signalling pathway and accumulation of prelamin A were also observed in the hair follicle stem cells of Zmpste24‐deficient mice, leading to their reduced proliferation capacity [67]. Mice carrying the progeric mutation LMNAΔ9 show compromised extracellular matrix synthesis, which is caused by reduced function of LEF1 due to inhibition of the Wnt signalling pathway [68].…”
Section: Lamin a And Lamin C In Development And Organogenesismentioning
confidence: 99%